Delays in the diagnosis of oral cancer due to the quarantine of COVID-19 in Córdoba, Argentina - Gilligan, Gerardo Marcelo (2020)
Fil: Gilligan, Gerardo Marcelo. Universidad Nacional de Córdoba. Facultad de Odontología. Departamento de Medicina Oral; Argentina.